A Case of Incus Necrosis Following Oral and Intratympanic Steroid Administration for Sensorineural Hearing Loss. Issue 9 (October 2020) - Kapoor, Elina; Sabetrasekh, Parisa; Monfared, Ashkan
Abstract : Objective: Intratympanic (IT) steroid injections are often used for the treatment of inner ear pathologies, including sudden sensorineural hearing loss. IT steroids are also commonly used in conjunction with or in case of systemic steroid therapy failure. They are viable options for patients who cannot endure side effects or are at high risk of complications from systemic therapy. The duration of treatment, strength, and type of steroid, and number of IT injections are important factors that impact possible treatment complications. Reported complications, though uncommon, include tympanic membrane perforation, otalgia, vertigo, otitis media, and acne. In this report, we explore a novel case of incus necrosis associated with oral and/or IT steroid administration. Study Design: Clinical Capsule Report. Setting: Tertiary Academic Center. Patient: We present a case of a 70-year-old male with sudden sensorineural hearing loss who developed incus necrosis and conductive hearing loss following treatment with oral and intratympanic steroids. Intervention: The patient underwent a left tympanoplasty with ossicular chain reconstruction to treat the conductive component of his hearing loss. Results: The left tympanoplasty almost fully-resolved the conductive component of his hearing loss. However, intraoperative and CT assessment of the temporal bone revealed resorption of the long process of the incus, with otherwise normal-appearing ossicles. Conclusion: We report the first case of possible steroid-induced necrosis of the long process of the incus. Owing to its tenuous blood supply, the incus may be predisposed to steroid-induced osteonecrosis similar to that of the femoral head.